Knee strength of professional basketball players - Theoharopoulos, A.; Tsitskaris, G.; Nikopoulou, M.; Tsaklis, P. (The Journal of Strength and Conditioning Research, 2000)
The influence of intensive and systematic training on the lower-extremity strength of professional basketball players has not yet been defined. The purpose of this study was to evaluate professional basketball players' concentric strength of knee extension and flexion and the full range of motion, using an isokinetic dynamometer at 60 and 180°·s1. The sample consisted of 12 male basketball players, all members of the same professional basketball team that has players in all playing positions. According to the results, there was no statistically significant difference between the dominant and the nondominant limb on the measures of peak torque, peak torque per body weight, work per repetition, and work per repetition to body weight ratio. There was a statistically significant increase in the ratio of peak torque in concentric flexion and extension of the knee with the increase in velocity. At the same time, the flexion-extension ratios of knees at 60 and 180°·s1 are outside the limits of the literature. Therefore, we conclude that hamstrings in these athletes present higher-than-normal values in strength when compared with the literature. At the velocity of 180°·s1, in flexion and extension, the values of peak torque and peak torque per body weight demonstrate greater strength in the nondominant limb in relation to the dominant. These results provide information about the existing relation between the dominant and the nondominant limb and the relation of flexors and extensors in concentric action, which seems to increase with the increase of velocity. The research encourages further study on basketball athletes and, more specifically, on the relation of flexors and extensors of the knee.